Halophilic rhizobacteria promote growth, physiology and salinity tolerance in Sesamum indicum L. grown under salt stress - Sridhar, Dharman; Alheswairini, Saleh S.; Barasarathi, Jayanthi; Enshasy, Hesham Ali El; Lalitha, Sundaram; Mir, Sajad Hussain; Nithyapriya, S.; Sayyed, Riyaz (Frontiers in Microbiology, 2025)
IntroductionSalt stress is a major global issue that negatively affects plant growth and physiological processes. Plant growth-promoting rhizobacteria (PGPR) are known to alleviate salt stress and promote plant growth. This study aimed to isolate and characterize salt-tolerant PGPR from salinity-affected soils in Tamil Nadu, India, and assess their potential to enhance growth and salt tolerance in sesame (Sesamum indicum L.).MethodsSalt-tolerant PGPR were isolated and screened for plant growth-promoting traits. One isolate, designated PAS1, demonstrated significant capabilities, including the production of indole-3-acetic acid (IAA; 48.56 μg ml−1), siderophore production (89.20 ± 0.65%), phosphate solubilization (7.8 mm zone of clearance), ammonia, and hydrogen cyanide (HCN) production. PAS1 was identified as Bacillus flexus. Sesame plants were inoculated with B. flexus and grown under different salt concentrations (0, 100, and 200 mM NaCl) for 45 days.ResultsInoculation with B. flexus significantly improved the biochemical parameters of sesame plants under salt stress, including increased chlorophyll content (4.4 mg g−1), proline (0.0017 mg g−1), soluble sugars (61.34 mg g−1), amino acids (1.10 mg g−1), and proteins (3.31 mg g−1). Additionally, antioxidant enzyme activities were enhanced, as indicated by DPPH scavenging activity (60.25%), superoxide dismutase (231.29 U mg g−1 protein), peroxidase (6.21 U mg g−1 protein), catalase (3.38 U mg g−1 protein), and a reduction in malondialdehyde (23.32 μmol g−1).DiscussionThe study demonstrates that inoculation with salt-tolerant B. flexus can effectively improve sesame plant growth and enhance tolerance to salt stress. These findings suggest that halo-tolerant PGPR strains like B. flexus could serve as promising biofertilizers to improve crop productivity in salt-affected agricultural soils.